Analysis of Effectiveness PBL-STEM to Improve Student’s Critical Thinking Skills - Noera Wahdaniyah; Rudiana Agustini; Tukiran Tukiran (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to analyze the effectiveness of PBL-STEM in improving students' critical thinking skills. Method: The method used in this research is the literature review method. A literature review is a type of research that collects data and information from various sources by collecting and analyzing. This study analyzes as many as two national and international articles that can be accounted for. The articles used were published in 2018-2022. The steps in this Literature review method are identifying topics, searching for and selecting relevant articles, analyzing and synthesizing the literature, and creating a conclusion. Results: (1) the application of the PBL model can improve students' critical thinking skills; (2) the integration of STEM in the learning process is also able to improve critical thinking skills because STEM provides opportunities for students to identify real-life problems and solve them, which is per the characteristics of PBL; (3) the integration between PBL and STEM can be applied and can provide more effective results in improving students' critical thinking skills. Novelty: ThisThis study discusses the analysis of how effective the integration of STEM and PBL from the latest journals so that this research can be used as a reference for making quality learning tools.